White Matter and Gray Matter Segmentation in Brain MRI Images Using PSO Based Clustering Technique - Kalavathi, P; Naganandhini, S (International Journal of Computer Sciences and Engineering, 2025)
Alzheimer’s disease is one of the brain disorders caused due to shrinkage of brain tissues, particularly the White Matter and Grey Matter. Many imaging modalities are used to acquire the image of human brain, in order to diagnose the disorder. MRI is widely used technique to detect Alzheimer’s disease. In this research work, we aimed to develop a computational method to quantify the brain tissue loss in MRI human head scans. In this proposed method, we used particle swam optimization (PSO) technique to find the optimal cluster centroids to segment the brain tissue. These segmented White Matter and Gray matter are further analysed to quantify the Alzheimer’s disease. The output of this method is quantitatively and qualitatively evaluated by the similarity measures – Jaccard, and Dice based on the expert segmented results